RANCANG BANGUN SISTEM KONTROL PENCARIAN DAYA KELUARAN MAKSIMUM TURBIN ANGIN MENGGUNAKAN LOGIKA FUZZY - Raditya Mataram, I Made Yoga; Mataram, I Made; Arta Wijaya, I Wayan (Jurnal SPEKTRUM, 2024)
Currently, the use of energy sourced from wind is developing as a power plant. The wind source can become electricity through the conversion of energy from wind turbines. Small-scale wind turbines generally use a type of Permanent Magnet Synchronous Generator (PMSG). This is an advantage in maintenance and reduces system costs because PMSG has the advantage of no excitation system and does not require a gearbox. The problem that often occurs is finding maximum efficiency at variations in wind speed. High efficiency at several variations of wind speed can produce maximum output power. In this paper, a wind turbine search control system for maximum output power (MPPT) was designed using fuzzy logic. Design fuzzy logic control using 2 inputs and 1 output. The simulation results from the MPPT wind turbine control system design using fuzzy logic show that the resulting performance is better or more stable.